Evaluation of adventure-based learning to grow national insight in children - Sofyan Adhi; Puji Yanti Fauziah; Suwithida Charungkaittikul (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
This research aims to evaluate: (1) adventure-based learning designs, (2) the success of adventure-based learning programs, and (3) unplanned but achievable goals by adventure-based learning programs. This research is evaluation research (evaluation research) with a qualitative approach; the evaluation model used is a goal-free evaluation model (Goal Free Evaluation). The population and sample in this study were all participants in adventure-based learning at Jogja Adventure Kids from December 2022 to June 2023, totaling 13 children. Additionally, there were nine parents of students and one manager from Jogja Adventure Kids. The location of this research is in an open/wild space organized by Jogja Adventure Kids. Data collection techniques encompass both primary data, such as direct interviews and observations, and secondary data, including document reviews. This research instrument consists of an observation guide, an interview guide, field notes, and documentation. Data validity was achieved through triangulation with multiple sources, methods, and time periods. The data analysis techniques used are display, reduction and drawing conclusions. The results of the research show that (1) evaluation of adventure-based learning design includes the material provided and learning methods, (2) evaluation of success contains good things and bad things, and (3) evaluation of unplanned but achievable goals includes being a vehicle for channeling energy excess and becoming a health investment.